ALAT PEMOTONG PLAT SISTEM GESER - Ismael Marjuki; Polonia, Betti Ses Eka; Rahmadi, Hairian (Pengelola Jurnal Politeknik Negeri Ketapang, 2024)
The process of cutting steel plates is often found in small and large industries. Cutting is also a process of separating and reducing one solid object into two or more that are directed, modifying, forming, and removing unnecessary parts using cutting tools. Some common problems when using a hand grinder are user safety from sparks and dust. In addition, physical injury factors due to misuse and broken discs or grinding wheels can also occur during operation. Based on this, the author designed a tool that can cut plates safely and neatly. This tool's advantage is that it is safer and more efficient because it uses a sliding system. A plate-cutting tool with a sliding system has dimensions of 126.5 cm frame length, 50 cm width, and 20 cm frame height. Process the plate-cutting tool frame using a hollow iron measuring 40x40 mm and a grinding machine with a speed of 12,000 rpm.